Environmental Action and PYD. Environmental Action as Asset and Contribution of Positive Youth Development - Diego Gomez-Baya; Gina Tomé; Cátia Branquinho; Margarida Gaspar de Matos (Erebea, 2020)
Positive Youth Development theory presents a strength-based conception of transition to adulthood in which positive outcomes appear as consequence of the alignment of youth individual skills and contextual developmental assets. PYD may emerge from environmental action because it allows for developing reasoning skills, decision-making skills, self-efficacy, optimism, good relationships and civic engagement, among other thriving outcomes. Moreover, because values, attitudes and behaviors formed in this life stage influences those in later life stages, youth environmental education deserves greater attention. Developing youth as active citizens creates positive environmental and social change that provides the basis for more sustainable communities. Considering environmental action as a context for PYD, educators or program managers should consider young people as contributors, letting them participate in shared decision making, critical reflection and possibility to inquiry, as well as providing meaningful participation, sense of belongness and authentic care. Some experiences in youth environmental action are reviewed and some recommendations are provided in order to design and implement programs to jointly promote sustainable communities and PYD.